2022
DOI: 10.1080/21655979.2022.2090608
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A deletion reduces sevoflurane-induced neurocognitive impairment in neonatal mice by inhibiting NF-κB signaling pathway

Abstract: We investigated the role of IL-17A in sevoflurane-inducedneurocognitive impairment in neonatal mice. Seventy-two wild-type (WT) and 42 IL-17A knockout (KO) neonatal mice were randomly divided into WT ( n = 36), IL-17A −/− ( n = 6), sevoflurane (Sev, n = 36), and IL-17A −/− + sevoflurane (IL-17A −/− + Sev, n = 36) groups. The latter two groups were give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Accretion of ROS as a consequence of As-promoted oxidative stress can interfere with inflammation pathways through protein kinase C activation as evidenced by elevated levels of pro-inflammatory cytokines [15]. IL-17A is a pivotal inflammatory mediator exacerbating chronic tissue inflammation, triggering multiple signaling molecules like TNF-α, IL-1β, and IL-6 [13,14]. To explore the specific role of taxifolin on hippocampal inflammation in NaAsO2-treated cells, we evaluated IL-17A and its related inflammatory cytokines including TNF-α, IL-1β and IL-6.…”
Section: Taxifolin Alleviates Oxidative Stress Promoted By Naaso2mentioning
confidence: 99%
See 1 more Smart Citation
“…Accretion of ROS as a consequence of As-promoted oxidative stress can interfere with inflammation pathways through protein kinase C activation as evidenced by elevated levels of pro-inflammatory cytokines [15]. IL-17A is a pivotal inflammatory mediator exacerbating chronic tissue inflammation, triggering multiple signaling molecules like TNF-α, IL-1β, and IL-6 [13,14]. To explore the specific role of taxifolin on hippocampal inflammation in NaAsO2-treated cells, we evaluated IL-17A and its related inflammatory cytokines including TNF-α, IL-1β and IL-6.…”
Section: Taxifolin Alleviates Oxidative Stress Promoted By Naaso2mentioning
confidence: 99%
“…IL-17A promotes secretion of pro-inflammatory cytokines, like IL-1β and IL-6, which aggravates the inflammatory response including cerebral ischemia-reperfusion injury and Alzheimer's disease [11,12]. According to recent research, IL-17A leads to impaired neurocognitive functions by activating downstream inflammatory pathways which may amplify inflammation via the secretion of IL-1β and IL-6 cytokines [13]. In addition, Yang et al reported that anti-IL-17A treatment alleviates neuroinflammation by reducing TNF-α, IL-1β, and IL-6 proinflammatory cytokines and oxidative damage via strengthening antioxidant defense mechanism in the hippocampus [14].…”
Section: Introductionmentioning
confidence: 99%